Comparative administrative law issues regarding central and local government - Alexandru, Ioan, 1939- (Adjuris, International Academic Publishers, 2018)
The purpose of this book is to study comparative administrative law in the main EU states and the United States of America and Canada and then to provide proposals for the modernization of Romanian public administration in order to increase administrative convergence and to better meet the needs of citizens. In this book, the author aims to realize a dynamic approach by looking at the contemporary challenges and perspectives of the future of the contemporary administrations and on the other hand the modifications to be made at the level of the Romanian administrative law to increase the degree.